2019
DOI: 10.2135/cropsci2018.12.0724
|View full text |Cite
|
Sign up to set email alerts
|

Application Timing Affects Tolerance of Zoysiagrass to Fluazifop‐P‐butyl and Safening Effect of Triclopyr

Abstract: 1789 RESEARCH Z oysiagrass (Zoysia spp.) is a warm-season turfgrass widely adopted in the transitional zone and southeastern regions of the United States due to good turf quality and low nutrient input requirements. Zoysiagrass exhibits more shade and winterkill tolerance than bermudagrass (Cynodon spp.), fewer disease and insect problems than St. Augustinegrass [Stenotaphrum secundatum (Walter) Kuntze], and moderate salinity tolerance and wear tolerance compared with other warm-season grasses (Patton, 2010;Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…However, as with most traits controlled by multiple mechanisms, environmental conditions also inevitably play a role in the outcome of herbicide applications, and fluazifop-P-butyl sensitivity in zoysiagrass has been documented to vary depending on the environment and time of the year (Liu et al. 2019b). This significantly increases the difficulty of breeding a commercial line that performs predictably under variable environmental conditions or during different times of the year.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as with most traits controlled by multiple mechanisms, environmental conditions also inevitably play a role in the outcome of herbicide applications, and fluazifop-P-butyl sensitivity in zoysiagrass has been documented to vary depending on the environment and time of the year (Liu et al. 2019b). This significantly increases the difficulty of breeding a commercial line that performs predictably under variable environmental conditions or during different times of the year.…”
Section: Resultsmentioning
confidence: 99%
“…Because the tolerance is a polygenic trait, research should be conducted to identify the responsible QTLs to enable the use of marker-assisted selection and avoid the need to regularly conduct herbicide-sensitivity screenings (Délye et al 2011;Gupta et al 2010;Schneider et al 1997). However, as with most traits controlled by multiple mechanisms, environmental conditions also inevitably play a role in the outcome of herbicide applications, and fluazifop-P-butyl sensitivity in zoysiagrass has been documented to vary depending on the environment and time of the year (Liu et al 2019b). This significantly increases the difficulty of breeding a commercial line that performs predictably under variable environmental conditions or during different times of the year.…”
Section: Response Variable Bmentioning
confidence: 99%
“…Another challenge is the stability of the tolerance trait. Liu et al (2017) reported that fluazifop-P-butyl injury varied depending on the time of the year when the application is made and that the magnitude of this seasonal effect on herbicide susceptibility was also influenced by the cultivar. Even if a line with a single tolerance mechanism were to be generated, the complex nature of fluazifop-P-butyl tolerance may lead to unstable phenotypes due to large genotype by environment interactions, and thereby may limit their commercial value.…”
Section: Practical Implicationsmentioning
confidence: 99%